2021
DOI: 10.26719/emhj.21.005
|View full text |Cite
|
Sign up to set email alerts
|

Key lessons from a mixed-method evaluation of a postnatal home visit programme in the humanitarian setting of Gaza

Abstract: Background: The World Health Organization recommends postnatal home visits (PNHVs) to improve maternal and newborn health. Evidence of PNHV effectiveness in humanitarian settings is limited. Aims: To evaluate PNHVs implemented in the constrained humanitarian context of Gaza. Methods: Qualitative data were obtained through key informant interviews, in-depth interviews and/or focus group discussions with women targeted by the programme, nontargeted women, husbands, and home visitors. These data were complemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 10 publications
(14 reference statements)
0
23
0
Order By: Relevance
“… 49 A postnatal home visits programme implemented in the Gaza strip showed that women included in the programme had improved breastfeeding practices, and it helped to reduce harmful traditional practices such as the application of oil and salt to the umbilical cord. 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 49 A postnatal home visits programme implemented in the Gaza strip showed that women included in the programme had improved breastfeeding practices, and it helped to reduce harmful traditional practices such as the application of oil and salt to the umbilical cord. 34 …”
Section: Resultsmentioning
confidence: 99%
“…32 In Myanmar and Gaza, programmes with community-based providers increased the number of PNC visits and report improvement in some newborn interventions such as skin-to-skin and breastfeeding practices (statistically significant findings in Myanmar). 34 59 …”
Section: Resultsmentioning
confidence: 99%
“…Need to coupling HIVST distribution with public information, education & communication through media & social marketing, relying on community health workers to mediate use of HIVST & ensure linkage to care. (de Vries, Hamad et al 2021) [ 31 ] Gaza Conflict Essential new-born care Mixed methods: qualitative informant interviews, in-depth interviews &/or focus group discussions secondary analysis of Ministry of Health annual reports, central statistics & MICSs. Women targeted by the programme, non-targeted women, husbands, & home visitors.…”
Section: Resultsmentioning
confidence: 99%
“…All of the newborn health publications focused on essential newborn care, including thermal care, clean cord care and breastfeeding practices. Study locations included North-East Nigeria (Borno State) [ 25 ], occupied Palestinian Territories (Gaza) [ 31 ], South Sudan [ 32 ], and refugee settlements in Uganda [ 35 ]. Studies in Nigeria and Uganda were exploratory assessments of the acceptability and implementation of global best practices for newborn care, independent of an intervention.…”
Section: Resultsmentioning
confidence: 99%
“…All the newborn health publications focused on essential newborn care, including thermal care, clean cord care and breastfeeding practices. Study locations included North-East Nigeria (Borno State) [30], occupied Palestinian Territories (Gaza) [31], South Sudan [32], and refugee settlements in Uganda [33]. Studies in Nigeria and Uganda were exploratory assessments of the acceptability and implementation of global best practices for newborn care, independent of an intervention.…”
Section: Characteristics Of Included Papersmentioning
confidence: 99%